2013
DOI: 10.1021/ml400036z
|View full text |Cite
|
Sign up to set email alerts
|

Crystallographic Investigation and Selective Inhibition of Mutant Isocitrate Dehydrogenase

Abstract: Mutations in isocitrate dehydrogenase (IDH), a key enzyme in the tricarboxylic acid cycle, have recently been found in ~75% glioma and ~20% acute myeloid leukemia. Different from the wild-type enzyme, mutant IDH1 catalyzes the reduction of α-ketoglutaric acid to D-2-hydroxyglutaric acid. Strong evidence has shown mutant IDH1 represents a novel target for this type of cancer. We found two 1-hydroxypyridin-2-one compounds that are potent inhibitors of R132H and R132C IDH1 mutants with Ki values as low as 120 nM.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
80
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(83 citation statements)
references
References 19 publications
2
80
0
Order By: Relevance
“…We determined the tertiary structures of IDH1(R132H) in complex with NADPH and compounds 16 and 22 to a resolution of 3.2 Å, similar to those reported previously. 16,19 Statistics for diffraction data and structural refinement are in Supporting Information Table S1. As shown in Figure 2A and Supporting Information Figure S1, the protein IDH1(R132H) was found to crystallize as a homodimer with one NADPH molecule co-crystallized in each protein subunit.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We determined the tertiary structures of IDH1(R132H) in complex with NADPH and compounds 16 and 22 to a resolution of 3.2 Å, similar to those reported previously. 16,19 Statistics for diffraction data and structural refinement are in Supporting Information Table S1. As shown in Figure 2A and Supporting Information Figure S1, the protein IDH1(R132H) was found to crystallize as a homodimer with one NADPH molecule co-crystallized in each protein subunit.…”
Section: Resultsmentioning
confidence: 99%
“…These observations were also found in our previous structures of IDH1(R132H) in complex with 1-hydroxypyridinone inhibitors (e.g., compound 2 ). 16 …”
Section: Resultsmentioning
confidence: 99%
“…These two possibilities cannot be distinguished here, but hopefully a crystal structure with a member of the phenyl-glycine series will be forthcoming. Currently, a crystal structure is available for IDH1 with NADPH (6), and a structure with a small molecule (1-hydroxypyridine 2-one scaffold) inhibitor was published (24).…”
Section: Discussionmentioning
confidence: 99%
“…AGI-5198 suppression of 2HG levels did not completely ameliorate the DNA hypermethylation phenotype in mutant IDH1 glioma cells, suggesting that mutant IDH1-mediated epigenetic dysregulation is not easily reversed (Rohle et al, 2013). Since AGI-5198 was discovered, several other inhibitors have been identified that reduce D-2HG production in both in vitro and in vivo models (Popovici-Muller et al, 2012; Zheng et al, 2013). Shortly after the discovery of AGI-5198, medicinal chemistry optimization yielded the first inhibitor of IDH2-R140Q (AGI-6780) that reversed the hematopoietic differentiation induced by IDH2-R140Q in TF-1 erythroleukemia cells (Wang et al, 2013).…”
Section: Allelic Inhibitors Of Mutant Idh1 and Idh2mentioning
confidence: 99%